2016
DOI: 10.4103/0972-2327.168631
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of stroke researches in India

Abstract: Currently, the stroke incidence in India is much higher than Western industrialized countries. Large vessel intracranial atherosclerosis is the commonest cause of ischemic stroke in India. The common risk factors, that is, hypertension, diabetes, smoking, and dyslipidemia are quite prevalent and inadequately controlled; mainly because of poor public awareness and inadequate infrastructure. Only a small number of ischemic stroke cases are able to have the benefit of thrombolytic therapy. Benefits from stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 68 publications
1
45
0
Order By: Relevance
“…This is because they not only affect the victim but also their caregiver, relatives, family, and society. [ 1 2 ] The impact of ischemic and hemorrhagic CVA in a developing country like India is still a subject of scrutiny. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…This is because they not only affect the victim but also their caregiver, relatives, family, and society. [ 1 2 ] The impact of ischemic and hemorrhagic CVA in a developing country like India is still a subject of scrutiny. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] A review performed by Banerjee and Das showed that poor availability of transport in rural areas and congestion in urban areas were considered constraints or barriers to immediate hospitalization and treatment initiation. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…There are limited published studies from India which have shown marked variation in the incidence of ICH complications of thrombolysis. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%